Efektivitas Model Somatic, Auditory, Visual, Intellectual dalam Meningkatkan Hasil Belajar IPA pada Materi Sistem Tata Surya - Anggun Budi Lestary; Aulia Azhar (Journal of Progressive Science Education, 2026)
Low science learning outcomes and teacher-centered instruction remain persistent challenges in Indonesian middle schools, leaving students disengaged and academically underperforming. Previous studies confirm that active, multisensory learning models produce better engagement and academic achievement than conventional approaches. This study examines the effect of the SAVI (Somatic, Auditory, Visual, Intellectual) learning model on science learning outcomes among seventh-grade students at SMPN 22 Padang. This study used a quantitative quasi-experimental design with a Non-equivalent Control Group Design. Purposive sampling selected class VII.H (n=32) as the experimental group and class VII.I (n=32) as the control group. The experimental group received three sessions of SAVI-based instruction totaling 15 lesson periods, while the control group received conventional instruction over the same duration. Instruments included a 24-item multiple-choice test, a learning model implementation observation sheet, and a student response questionnaire. Data analysis applied descriptive statistics, normality and homogeneity tests, an independent-samples t-test, and N-Gain analysis. SAVI model implementation reached a mean of 92%. The independent-samples t-test showed a statistically significant difference in posttest scores between groups, t(62) = 3.52, p = 0.001, d = 0.88. The experimental group achieved a mean posttest of 70.84 (SD = 14.90) compared to 58.44 (SD = 13.24) in the control group. N-Gain analysis confirmed the experimental group's learning improvement was significantly higher, t(62) = 9.44, p < 0.001, d = 2.36, with means of 0.478 (medium category) versus 0.176 (low category). The student response questionnaire yielded 84.47%, indicating positive student acceptance of the model. Within the context of this study, the SAVI learning model produced significantly better science learning outcomes compared to conventional instruction. These findings apply specifically to the sample and material studied and should not be generalized without further replication.